Blow-Up Criteria for the Modified Novikov Equation - Caochuan Ma; Wujun Lv (Abstract and Applied Analysis)
We investigate the Cauchy problem for the modified Novikov equation. We establish blow-up criteria on the initial data to guarantee the corresponding solution blowing up in finite time.